Clinicoepidemiological Study of Different Types of Warts - Shruti S. Ghadgepatil; Sanjeev Gupta; Yugal K. Sharma (Dermatology Research and Practice)
Background. Warts are cutaneous and, sometimes, mucosal lesions caused by one of the several human papilloma viruses. Aim. Assessment of the clinicoepidemiological aspects of warts. Materials and Methods. One hundred consecutive patients of warts presenting to the department of our institution were assigned two broad locational groups: genital and nongenital warts, the latter subdivided into common, plane, palmoplantar, mosaic, and digitate/filiform. Results. Ninety had nongenital and 10 had genital warts in our study; common (42%), palmoplantar (20%), and plane (18%) were the common types of the nongenital warts. All the genital warts were acuminate. In the second decade, the commonest age group, encompassed all patients of mosaic, 40% of palmoplantar, and 20% of genital warts. Overall male (66%) preponderance xisted. All cases of filiform warts were males. Mosaic warts affected females more commonly. Students (32%), laborers (28%), and housewives (16%) were the usual occupations. Cosmetic concern (92%), pain (16%), and itching (15%) were the common complaints. All patients of genital warts sought treatment within 6 months. Conclusions. Common, palmoplantar, and plane warts were the common types of nongenital warts. Overall prevalence peaked during the second decade but one-third of the cases of plane warts occurred during the first. Extremities were the most common sites (66.7%); face was the next commonly (23%) involved.